“A Sense of an Absent Future.” Pervading Post-apartheid South African Literature: Re-conceptualisations of Temporality in André Brink’s Transitional Writings - Grzęda, Paulina (Werkwinkel, 2019)
Numerous commentators have recently indicated a prevailing sense among South africans of a historical repetition, a pervasive sentiment that the country has failed to shake off the legacy of apartheid, which extends into the present, and possibly also the future. 1 Such an observation has led South African psychologist, derek Hook, to conclude that in order to adequately address the post-apartheid reality and allow the process of working through trauma, there is a need to abandon the linear Judeo-Christian model of time derived from the Enlightenment. Instead, Hook advocates to start thinking of post-apartheid South Africa not as a socio-economically or racially stratified society, but rather as a country of unsynchronized, split, often overlapping temporalities. Thus, he offers to perceive of ‘chaffing temporalities’ of the contemporary predicament. Resende and Thies, on the other hand, call for a need for a reconceptualised approach to temporality not only when dealing with heavily traumatized postcolonial countries such as South Africa, but more generally when addressing the geopolitics of all the countries of the so-called ‘Global South.’ My paper will discuss the manner in which reconceptualised postcolonial temporality has been addressed by South African transitional writings by André Brink. I will argue that, although Brink’s magical realist novels of the 1990s imaginatively engage with ‘the chaffing temporalities’ of the post-apartheid predicament, their refusal to project any viable visions of the country’s future might ultimately problematise the thorough embrace of Hook’s ‘ethics of temporality.’